2017
DOI: 10.1002/acr.23257
|View full text |Cite
|
Sign up to set email alerts
|

Internet Cognitive–Behavioral Therapy for Depression in Older Adults With Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Objective. To determine the efficacy of an internet-based cognitive-behavioral therapy (iCBT) program for depression in older adults with osteoarthritis (OA) of the knee and comorbid major depressive disorder (MDD). Methods. We conducted a randomized controlled trial in 69 adults (ages ≥50 years) meeting criteria for MDD and OA of the knee with 1-week postintervention (week 11) and 3-month followup (week 24) end points. Patients were allocated to either a 10-week iCBT program for depression added to treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 50 publications
(49 reference statements)
0
98
0
Order By: Relevance
“…However, one data set was duplicated and published in two different manuscripts38 39; therefore, the later one was excluded 38. From the 23 studies included in this SR, most studies (n=19) evaluated QoL,39–57 one study evaluated self-efficacy,56 one study evaluated helplessness,58 one evaluated pain catastrophising,56 two evaluated coping strategies,56 59 one evaluated depression and psychological distress,60 and one evaluated cognitive symptom management (CSM)61 in individuals with knee OA. The study of Broderick et al 56 considered more than one outcome as primary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one data set was duplicated and published in two different manuscripts38 39; therefore, the later one was excluded 38. From the 23 studies included in this SR, most studies (n=19) evaluated QoL,39–57 one study evaluated self-efficacy,56 one study evaluated helplessness,58 one evaluated pain catastrophising,56 two evaluated coping strategies,56 59 one evaluated depression and psychological distress,60 and one evaluated cognitive symptom management (CSM)61 in individuals with knee OA. The study of Broderick et al 56 considered more than one outcome as primary.…”
Section: Resultsmentioning
confidence: 99%
“…There was limited evidence from one study60 with medium effect that an internet-based cognitive behaviour therapy on depression improves depression in individuals with knee OA compared with treatment as usual (SMD=1.01, CI 1.55 to 0.47) (figure 6). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified one systematic review of psychological interventions for OA in any joint, as well as three RCTs that investigated a group-mediated cognitive behavioural physical activity intervention, motivational interviewing, and group acceptance commitment therapy. This builds on studies identified in the 2017 year in review, which evaluated effects of internet cognitive behaviour therapy for depression 72 , behavioural interventions 73 , as well as pain coping skills training in combination with therapeutic exercise 74,75 . Our findings suggest that psychological interventions may be useful adjuncts to core treatments for knee OA, such as exercise, until long-term efficacy can be established.…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs were published about education in patients with knee OA 30,31 . Twenty-five RCTs 14,15,18,32e53 were published about exercise for patients with knee OA (including three about Tai Chi, Yoga or other traditional Chinese exercises 48e50 and four about the combination of education and exercises 18,51e53 ).…”
Section: New Insights In Education and Exercise For Knee Oamentioning
confidence: 99%